Exploring the Effects of Academic Motivation and Socioeconomic Factors on Entrepreneurial Intention: A Mediated Model of Self-Efficacy among Students - Muhammad Jufri; Andika Isma; Hajar Dewantara; Andi Naila Quin Azisah Alisyahbana; Sitti Hajerah Hasyim (CV. Sakura Digital Nusantara, 2025)
Students in entrepreneurship study programs possess substantial potential to become future entrepreneurs. However, their entrepreneurial intention is influenced by various internal and external factors. This study aims to examine the direct and indirect effects of academic motivation and parental socioeconomic status on students’ entrepreneurial intention, with self-efficacy as a mediating variable. A quantitative approach with a descriptive explanatory design was employed to analyze the relationships among variables. The population consisted of students enrolled in the Entrepreneurship Study Program at the Faculty of Economics and Business, Universitas Negeri Makassar (FEB UNM). A total of 75 students were selected using proportional random sampling. Data were processed using SPSS version 27. The findings revealed that academic motivation does not have a direct effect on entrepreneurial intention but has a positive and significant effect on self-efficacy. Parental socioeconomic status significantly and positively affects both self-efficacy and entrepreneurial intention. Although self-efficacy shows a positive influence on entrepreneurial intention, the effect is not statistically significant. However, both academic motivation and parental socioeconomic status have positive and significant indirect effects on entrepreneurial intention through self-efficacy. The study suggests that the Entrepreneurship Study Program should place greater emphasis on strategies that enhance students' self-efficacy and entrepreneurial intention.